Tuberculosis una creciente amenaza para los trabajadores y estudiantes del área de salud - Nieto Ramirez, Luisa María (Universidad Santiago de Cali, 2020)
Tuberculosis is a chronic infectious disease, caused by Mycobacterium tuberculosis, a bacterium identified by Robert Koch in 1882 and that after a little more than a century, is recognized as the leading cause of death due to an infectious disease. TB usually affects the lungs, but it can also affect other organs. Because its transmission is from person to person by inhalation of droplet-containing-bacteria suspended in the air, this disease is a public health concern. Daily, health workers are exposed to numerous hazards, including close contact with infectious patients and their potentially contaminated environment. It is estimated that about 1,000 health workers contract HIV,for reasons of their work and it is presumed that cases of tuberculosis, exceeds this number. Among the factors that explain the risk of infection with the consequent development of active TB are: the number of patients with TB treated, the function or occupation, the workplace, the delay in the diagnosis of patients and most importantly the lack of biosafety policies and measures in work environments, which facilitates direct exposure. We present here a current review of the status of occupational TB in the city of Cali during 2015 to 2017. This work was supported by the city's municipal health secretariat and the TB program. We emphasize the importance of continuing the evaluation of this disease in vulnerable populations such as health workers and evaluate the preventive measures suggested by international agencies (Pan American Health Organization and Center for Disease Control) to mitigate the impact of TB in the city.